Danmarks Kirker. Ribe amt. 2. bd., 16. hefte. Århus amt. 5. bd., 30-31. hefte. Udgivet af Nationalmuseet. (Poul Kristensens Forlag, 1987). 137-154 s. - Søgaard, Helge (Historie/Jyske Samlinger, 1989)
-